PENGARUH VARIASI SIRIP ISOLATOR POLYETHYLENE TERHADAP TINGKAT ARUS BOCOR DAN TEGANGAN FLASHOVER PADA KONDISI KERING DAN BASAH - Fransiskus X. H. Keraf; Moch. Dhofir; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2023)
This study describes the effect of variations in the sleeve fins on polyethylene insulators on the level of leakage current and flashover voltage in dry and wet conditions. This research begins with data collection by testing the leakage current and breakdown voltage at the High Voltage Laboratory, Department of Electrical Engineering, Faculty of Engineering, Universitas Brawijaya. The various conditions used in testing the leakage current and flashover voltage include dry conditions and wet conditions with different wetting rates, namely 10 mL/s, 30 mL/s, and 60 mL/s. Tests were carried out using high AC voltage on three types of insulators, namely type A, type B, and type C. The arrangement of the electrodes used was rods. The results obtained in this study are the influence of the variation of the fin arm on the level of leakage current and flashover voltage. Where the insulator that has the lowest level of leakage current is the type B insulator with the size of the upper fin which is longer than the lower fin. This is influenced by the upper fin of the insulator which resembles a hood, which when wet conditions cause the water not to completely hit the lower fin. Where the greater the value of the wetting discharge, the greater the value of the leakage current and the greater the surface resistance and power losses. This type B isolator has the best resistance because it also experiences flashover at the highest test voltage level. Index terms : Polyethylene Insulator, Leakage Current, Wetting Discharge, Flashover Voltage